Shear rheological properties of composite fluids and stability of particle suspensions: Potential implications for fracturing and environmental fluids. (25th March 2019) - Pensini, Erica; Rodriguez, Braulio Macias; Marangoni, Alejandro G.; Collier, Christopher M.; Elsayed, Abdallah; Siwik, Amanda
Abstract : Composite fluids are comprised of particles and polymers and are used for fracking and the in‐situ treatment of subsurface contaminants. This study investigates the correlation between the shear viscoelasticity of guar aqueous solutions and their effectiveness in suspending sand, which is a common fracking proppant. In the absence of a crosslinker, the shear viscous modulus (G") of 5 g/L guar solutions was greater than the shear elastic modulus (G'). When the crosslinker borax was added, the guar solutions behaved as yield stress fluids (G' > G"). Sand was well‐suspended in the crosslinked guar solutions but settled in non‐crosslinked fluids. Similar results were obtained with fenugreek gum. This study also investigates the correlation between particle settling and the effect of particle addition on the rheology of the fluids. Granulated activated carbon (GAC) particles are utilized to remediate polluted sites and were used as model particles. Guar and xanthan effectively suspended the GAC. Anionic polyacrylamide effectively suspended the GAC but not after soaking in sodium dodecyl sulphate. Zetag 8167 did not effectively suspend the GAC. The addition of 10 g/L of GAC did not affect the shear rheology of the fluids that suspended them, but decreased the shear viscoelastic moduli of the polymeric fluids that could not suspend them. Abstract : Correlation between changes in the rheology of polymeric fluids upon particle addition and particle settling.